Estrategias para fortalecer el desarrollo de la motricidad fina en los estudiantes de preescolar del Colegio Alegría Del Niño Riohacha – Guajira (2021)
This monographic research proposal refers to improving fine motor skills in boys and girls from 3 to 6 years of age, due to the importance it has in initial education. As is known to all teachers, when they are young they experiment with great enthusiasm through play, since they manipulate objects directly with their hands; through From all this they develop their creativity and learn to become autonomous, self-confident and have a better personality, since preschool education is in charge of creating the bases for the formation of the initial stage, therefore it is a period of great relevance for children. boys and girls. Considering all this, fine motor skills is one of the skills on which the desired levels have not yet been reached in preparation for preschool.